Usate of Filter Tube to Reduce Pb, Turbidity And Increase pH of Rain Water Flowing Through Zinc Rooftop House (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Pb contained in rain water comes from zinc rooftop, beside that, it comes from the pollutant dissolved and comes into rain water reservoir and is used for community drinking water source. This research objective is to evaluate Pb, pH and turbidity of rain water before and after process and to analyze efectivity of shell sand filtration and activated carbon absorbtion in the filter tube to decrease Pb and turbidity and increase pH of rain water. This research is an experiment with pre and post test design with control and observational with cross sectional design. It is conducted in Pontianak and Kubu Raya West Kalimantan in 2016 with two target regions which represent urban and rural ones. The result indicated that average lead (Pb) contained in rain water and turbidity process is high with 131.7 µg/l and 20 NTU and pH is low with 5.2. After process, Pb become 0.71 µg/l and turbidity become 5.66 NTU while pH increases to 6.9. The effectivity of filter tube to reduce lead (Pb) contained in rain water is 99.4% and to reduce turbidity is 72%.